PENGARUH MODEL PEMBELAJARAN VCT (VALUE CLARIFICATION TECHNIQUE) TERHADAP KETERAMPILAN MENULIS SISWA KELAS IV SDN 22 BELOPARANG KABUPATEN BANTAENG - Syartika, Dewi; Syakur, Abdan; Rajab, Abd (Progressive of Cognitive and Ability, 2024)
The main problem in this research is how the VCT learning model influences the poetry writing skills of class IV students at Sdn 22 Beloparang Kab. Bantaeng. This research aims to describe the influence of the VCT (Value Clarification Technique) learning model on poetry writing skills in class IV students at SDN 22 Beloparang Kab. Bantaeng. The results of research in the experimental class obtained an average pretest score of 41.66% while the average posttest score was 72.22%. Meanwhile, the results of the hypothesis test show that the values ​​obtained are tcount = 2.93 and ttable = 1.77, so tcount>ttable or 2.93>1.77 is obtained, so Hi is accepted and HO is rejected. Based on the research results above, it can be concluded that the VCT learning model has an influence on Indonesian language learning outcomes for class IV students at SDN 22 Beloparang Kab. Bantaeng.